5-Acetyl-3-hydroxy-4-phenyl-4,5-dihydro-1H-1,5-benzodiazepin-2(3H)-one - Rida, M.; Alsubari, A.; Essassi, E.M.; Zouihri, H.; Ng, S.W. (International Union of Crystallography, 2011)
In the title compound, C(17)H(16)N(2)O(3), the seven-membered diazepine ring adopts a boat conformation with the hydroxy-substituted C atom at the prow and fused benzene ring C atoms at the stern. The phenyl substituent occupies an equatorial position. The amino group of the ring system is a hydrogen-bond donor to the oxo O atom of an inversion-related molecule, and the hydroxy group is a hydrogen-bond donor to the acetyl O atom of another inversion-related molecule. The two hydrogen bonds generate a ribbon motif parallel to [101] in the crystal structure.